A Laboratory of Extremophiles: Iceland Coordination Action for Research Activities on Life in Extreme Environments (CAREX) Field Campaign - Marteinsson, Viggó (MDPI, 2013)
Existence of life in extreme environments has been known for a long time, and their habitants have been investigated by different scientific disciplines for decades. However, reports of multidisciplinary research are uncommon. In this paper, we report an interdisciplinary three-day field campaign conducted in the framework of the Coordination Action for Research Activities on Life in Extreme Environments (CAREX) FP7EU program, with participation of experts in the fields of life and earth sciences. In situ experiments and sampling were performed in a 20 m long hot springs system of different temperature (57 °C to 100 °C) and pH (2 to 4). Abiotic factors were measured to study their influence on the diversity. The CO(2) and H(2)S concentration varied at different sampling locations in the system, but the SO(2) remained the same. Four biofilms, mainly composed by four different algae and phototrophic protists, showed differences in photosynthetic activity. Varying temperature of the sampling location affects chlorophyll fluorescence, not only in the microbial mats, but plants (Juncus), indicating selective adaptation to the environmental conditions. Quantitative polymerase chain reaction (PCR), DNA microarray and denaturing gradient gel electrophoresis (DGGE)-based analysis in laboratory showed the presence of a diverse microbial population. Even a short duration (30 h) deployment of a micro colonizer in this hot spring system led to colonization of microorganisms based on ribosomal intergenic spacer (RISA) analysis. Polyphasic analysis of this hot spring system was possible due to the involvement of multidisciplinary approaches.